2002
DOI: 10.4049/jimmunol.169.2.920
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophil-Expressed CD28 Interacts with Macrophage B7 to Induce Phosphatidylinositol 3-Kinase-Dependent IFN-γ Secretion and Restriction of Leishmania Growth

Abstract: We previously showed that CD28 is expressed on human peripheral blood neutrophils and plays an important role in CXCR-1 expression and IL-8-induced neutrophil migration. In this work we demonstrate that Leishmania major infection of macrophages results in parasite dose-dependent IL-8 secretion in vitro and in IL-8-directed neutrophil migration, as blocked by both anti-IL-8 and anti-IL-8R Abs, toward the L. major-infected macrophages. In the neutrophil-macrophage cocultures, both CTLA4-Ig, a fusion protein that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
(34 reference statements)
2
23
2
1
Order By: Relevance
“…4 Using an end-point titration assay, we could demonstrate that the number of viable Leishmania remained stable inside PMN 18 and 42 h after infection (62.1 Ϯ 3.1 and 59.3 Ϯ 2.9 Leishmania per 1000 PMN, respectively, n ϭ 4). Although these findings appear to contradict some earlier reports indicating that the PMN exert antileishmanial activity (10,11), the data confirm other studies describing the diseasepromoting effect of PMN in Leishmania infection (12,13). Importantly, our data are in line with the recent observation that apoptotic PMN exacerbate Leishmania infection (14).…”
Section: Resultscontrasting
confidence: 54%
“…4 Using an end-point titration assay, we could demonstrate that the number of viable Leishmania remained stable inside PMN 18 and 42 h after infection (62.1 Ϯ 3.1 and 59.3 Ϯ 2.9 Leishmania per 1000 PMN, respectively, n ϭ 4). Although these findings appear to contradict some earlier reports indicating that the PMN exert antileishmanial activity (10,11), the data confirm other studies describing the diseasepromoting effect of PMN in Leishmania infection (12,13). Importantly, our data are in line with the recent observation that apoptotic PMN exacerbate Leishmania infection (14).…”
Section: Resultscontrasting
confidence: 54%
“…ϩ PMNs have been shown to activate Leishmania-infected macrophages to produce IFN-␥ via the CD28-CD80/CD86 pathway [24]. As a result of the lack of CD28 expression on PMNs before and during coculture with DCs, this pathway cannot be involved in the interactions reported here.…”
Section: Discussioncontrasting
confidence: 39%
“…3A), an usually T lymphocyte-associated costimulatory molecule, which has been shown to be expressed on a PMN subset [24]. The proportion of dead or apoptotic PMNs was similar in control and cocultured PMNs (Fig.…”
Section: Clustering and Phenotypic Changes Of Cocultured Pmns And Dcsmentioning
confidence: 84%
See 1 more Smart Citation
“…Nonetheless, other mechanisms of cross-talk between infected macrophages and neutrophils have been described previously, such as the transfer of lactoferrin (41) and myeloperoxidase (42) and, more recently, the presence of neutrophil granules that colocalized with intracellular mycobacteria (43). It was also shown that the CD28/ CD80-CD86 interaction on neutrophil/macrophages induces IFN-␥ production, restricting the growth of L. major (44). Importantly, the mechanisms leading to cure and resistance to Leishmania infection are associated with macrophage activation, resulting from TNF-␣-and IFN-␥-induced production of free radicals and ultimately with destruction of the intracellular parasites (45,46).…”
Section: Discussionmentioning
confidence: 77%